GEOPOLITICAL, HISTORICAL, MENTAL FACTOR OF THE POWER OF STATES: ATTEMPT Of ANALYSIS - Варич, Д. Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
Two states are analyzed through the prism of their legal capacity. The historical, mental, and geopolitical factor of the legal capacity is considered. The degree of influence of these factors on the current state of nations is established. The attention is focused on the presence or absence of the armed conflicts. Possible development prospects for the most incompetent states are determined.